Utilizing Sleep Education to Reduce Postpartum Mood Disorder in New Mothers - Osorio, Virginia; Martin, Daniel (Journal of Maternal and Child Health, 2023)
Background: Infant sleep biology and maternal intuition challenge the idea of behavioral sleep training being authoritative knowledge in Western society. Behavioral sleep training may increase stress levels in postpartum mothers who feel conflicted and wish to use alternative methods. The aim of this study was to determine whether having access to infant sleep education improves maternal mental health.Subjects and Method: A quasi-experimental pretest-posttest design using web-based surveys was used to assess the impact of a three-week virtual infant sleep education program on the dependent variables of depression outcomes and consolidated infant sleep. The target population were postpartum women between the age of 18 and 50. Sample size was 18 subjects were recruited through convenience and criterion sampling. Pre-tests and post-tests included nominal questions, Likert scale items, and the Edinburg Postnatal Depression Scale (EPDS). Analysis included difference analyses, Shaprio-Wilk normality checks, Spearman’s rho and Bayes factor bounds.Results: The average improvement on the EPDS was a decrease of 1.89 points, 95% CI= -∞ to 0.11; p= 0.116), VS-MPR = 1.47, with the highest magnitude of improvements in domains regarding feelings of failure if their baby does not sleep through the night (r= 0.78; 95% CI= 0.40 to ∞; p= 0.012, desire to sleep train (r= 0.50; 95% CI = -0.10 to ∞; p= 0.091) and decreased feelings of self-blame (r= 0.34; 95% CI= -0.13 to ∞; p = 0.080).Conclusion: Sleep education can be beneficial in reducing stress related to infant sleep and feelings of failure as a parent in postpartum women. Keywords: behavioral training, maternal mental health, sleep education, postpartum depression. Correspondence: Virginia Osorio. Shenandoah University, 1460 University Drive, Winchester, VA 22601. vosorio-19@su.edu.